Articulation, Agency and Embodiment in Contemporary Pakistani Urdu Poetry by Women - Mansoor, Asma; Arif, International Islamic University, Islamabad, Pakistan, Najeeba (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper explores the notions of â€œarticulation,â€ â€œagencyâ€ and â€œembodimentâ€ in Urdu poetry composed by Pakistani women. Although these terms have been taken from the First world feminist discourses, we aim to highlight how these three terms were not merely reflected in the contemporary poetry of Pakistani women, but rather were used to express their own modalities and associations as they countered the patriarchal system within which they were embedded. Our study does not simply apply these terms on selected poems by Kishwar Naheed (1940-), Fehmeeda Riaz (1946-) and Azra Abbas (1948-), but it also explores how these terms undergo a discursive diffraction as the Pakistani woman is no longer seen as a subaltern entity with a silenced subjectivity. We have taken on board the synonymic idea of writing as an agentive act of embodiment, as theorised by Luce Irigaray and HÃ©lÃ¨ne Cixous. This is to show that while these terms were theorised by Western feminists, contemporary Pakistani women writers have, over the last few decades, been enacting these terms in ways which deny the stereotypical projection of the Third world woman in the Western gender discourses. For these women writers, writing enacts embodiment through articulation and thus agentively counters the objectifying gaze of the patriarchal order.